Age-related differences in hair trace elements: a cross-sectional study in Orenburg, Russia. (2nd September 2016) - Skalnaya, Margarita G.; Tinkov, Alexey A.; Demidov, Vasily A.; Serebryansky, Eugeny P.; Nikonorov, Alexandr A.; Skalny, Anatoly V.
Abstract: Background : Age-related differences in the trace element content of hair have been reported. However, some discrepancies in the data exist. Aim : The primary objective of this study was to estimate the change in hair trace elements content in relation to age. Subjects and methods : Six hundred and eighteen women and 438 men aged from 10–59 years took part in the current cross-sectional study. Results and conclusions : Hair Cr, Mn, Ni, Si, Al, As, Be, Cd and Pb tended to decrease with age in the female sample, whereas hair Cu, Fe, I, Se, Li and Sn were characterised by an age-associated increase. Hair levels of Cr, Cu, I, Mn, Ni, Si and Al in men decreased with age, whereas hair Co, Fe, Se, Cd, Li and Pb content tended to increase. Hair mercury increased in association with age in men and in women, whereas hair vanadium was characterised by a significant decrease in both sexes. The difference in hair trace element content between men and women decreased with age. These data suggest that age-related differences in trace element status may have a direct implication in the ageing process.